Effects of Four-Day School Weeks on Student Achievement: Evidence from Oregon - Paul N. Thompson (Institute of Labor Economics (IZA), 2019)
Due to increased financial pressures following the Great Recession, a growing number of school districts have switched from a traditional five-day school week to a four-day week schedule. While these shorter school weeks potentially help reduce costs, this study considers the implications these school schedules have on student achievement. This study uses a difference-in-differences analysis using a panel data set of student-level test scores to examine the effects of the adoption of these four-day school weeks on student achievement in the State of Oregon from 2007-2015. I find that these school schedules have detrimental impacts on student achievement, with declines of between 0.044 and 0.053 standard deviations in math scores and declines of 0.033 and 0.038 standard deviations in reading scores. The results suggest that four-day school weeks are more detrimental for the math and reading achievement of boys and the reading achievement of low-income students. Earlier school start times and lost instructional time of nearly three and a half hours a week appear to be the primary mechanisms underlying these achievement losses.
Keywords: I21; 330; four-day school weeks; student achievement; instructional time